Multimorbidity increases the risk of dementia: a 15 year follow-up of the SHARE study. (18th April 2023) - Veronese, Nicola; Koyanagi, Ai; Dominguez, Ligia J; Maggi, Stefania; Soysal, Pinar; Bolzetta, Francesco; Vernuccio, Laura; Smith, Lee; Matranga, Domenica; Barbagallo, Mario
Abstract: Aims: the literature regarding the association between multimorbidity and dementia is still unclear. Therefore, we aimed to explore the potential association between multimorbidity at the baseline and the risk of future dementia in the SHARE (Survey of Health, Ageing and Retirement in Europe) study, a large European research survey, with a follow-up of 15 years. Methods: in this longitudinal study, multimorbidity was defined as the presence of two or more chronic medical conditions, among 14 self-reported at the baseline evaluation. Incident dementia was ascertained using self-reported information. Cox regression analysis, adjusted for potential confounders, was run and hazard ratios (HRs), with their 95% confidence intervals (CIs), that were estimated in the whole sample and by 5 year groups. Results: among 30, 419 participants initially considered in wave 1, the 23, 196 included participants had a mean age of 64.3 years. The prevalence of multimorbidity at baseline was 36.1%. Multimorbidity at baseline significantly increased the risk of dementia in the overall sample (HR = 1.14; 95% CI: 1.03–1.27) and in participants younger than 55 years (HR = 2.06; 95% CI: 1.12–3.79), in those between 60 and 65 years (HR = 1.66; 95% CI: 1.16–2.37) and in those between 65 and 70 years (HR = 1.54; 95% CI: 1.19–2.00). In the overall sample, high cholesterol levels, stroke, diabetes and osteoporosis increased the risk of dementia, particularly if present among participants between 60 and 70 years of age. Conclusions: multimorbidity significantly increases the risk of dementia, particularly in younger people, indicating the need for early detection of multimorbidity for preventing cognitive worsening.